2023
DOI: 10.3390/microorganisms11030643
|View full text |Cite
|
Sign up to set email alerts
|

Application of Magnetite-Nanoparticles and Microbial Fuel Cell on Anaerobic Digestion: Influence of External Resistance

Abstract: In this paper, the application of magnetite-nanoparticles and a microbial fuel cell (MFC) was studied on the anaerobic digestion (AD) of sewage sludge. The experimental set-up included six 1 L biochemical methane potential (BMP) tests with different external resistors: (a) 100 Ω, (b) 300 Ω, (c) 500 Ω, (d) 800 Ω, (e) 1000 Ω, and (f) a control with no external resistor. The BMP tests were carried out using digesters with a working volume of 0.8 L fed with 0.5 L substrate, 0.3 L inoculum, and 0.53 g magnetite-nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Yaqoob et al (2023) used rotten rice as a substrate in their MFC, showing an internal resistance of 312.5 Ω using graphite as electrodes. They also mentioned that the increase in internal resistance decreased the mobility of electrons [61]. Likewise, Raychaudhuri et al (2023), in their MFCs, used rice mill wastewater as a substrate, achieving an internal resistance of 372.34 Ω using carbon electrodes, mentioning that high absorbed values of the chemical oxygen demand were due to the high porosity shown of the electrodes [62].…”
Section: Results and Analysismentioning
confidence: 99%
“…Yaqoob et al (2023) used rotten rice as a substrate in their MFC, showing an internal resistance of 312.5 Ω using graphite as electrodes. They also mentioned that the increase in internal resistance decreased the mobility of electrons [61]. Likewise, Raychaudhuri et al (2023), in their MFCs, used rice mill wastewater as a substrate, achieving an internal resistance of 372.34 Ω using carbon electrodes, mentioning that high absorbed values of the chemical oxygen demand were due to the high porosity shown of the electrodes [62].…”
Section: Results and Analysismentioning
confidence: 99%
“…The coulombic efficiency relies on the impedance or resistance of a bioelectrochemical system, and higher resistance leads to a decrease in the coulombic efficiency since it is difficult to retrieve electrons from a system with higher resistance [48] . Thus, the very high coulombic efficiency on the MFCMM digester is an indication that this digester recovered the greatest number of electrons [49] . Zhou et al [50] investigated the effect of static magnetic field on a bioelectrochemical system and found that static magnetic field reduced the internal resistance, particularly its diffusion resistance.…”
Section: Resultsmentioning
confidence: 99%
“…[48] Thus, the very high coulombic efficiency on the MFCMM digester is an indication that this digester recovered the greatest number of electrons. [49] Zhou et al [50] investigated the effect of static magnetic field on a bioelectrochemical system and found that static magnetic field reduced the internal resistance, particularly its diffusion resistance. Furthermore, due to low resistance, the use of static magnetic field resulted in abundance of Geobacter of almost 32.5%, and the high syntrophic interactions between exoelectrogenic and methanogenic microorganisms resulted in higher coulombic efficiency.…”
Section: Electrochemical Characterizationmentioning
confidence: 99%